HUBUNGAN TINGKAT KEPARAHAN GEJALA DAN STATUS FUNGSIONAL PADA PASIEN CARPAL TUNNEL SYNDROME DIUKUR MENGGUNAKAN CARPAL TUNNEL SYNDROME ASSESSMENT - Alif Luqman Hakim; Robby Tjandra (Jurnal Kedokteran Diponegoro, 2016)
Background :  Carpal Tunnel Syndrome is an entrapment neuropathy due to pressure on the median nerve with one of the early symptom is pain. Pain that is present in patients with Carpal Tunnel Syndrome can make impairment of hand function, resulting in functional limitations to patients with Carpal Tunnel Syndrome in performing everyday activities.